2009
DOI: 10.1038/ijo.2009.100
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical alterations of skeletal muscles from the genetically obese (ob/ob) mouse

Abstract: Background: Knowledge of the morphological and biochemical alterations occurring in skeletal muscles of obese animals is relatively limited, particularly with respect to non-limb muscles and relationship to fibre type. Objective: Sternomastoid (SM; fast-twitch), extensor digitorum longus (EDL; fast-twitch), and soleus (SOL; mixed) muscles of ob/ob mouse (18-22 weeks) were examined with respect to size (mass, muscle mass-to-body mass ratio, cross-sectional area (CSA)), fibre CSA, protein content, myosin heavy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 46 publications
2
69
0
Order By: Relevance
“…Thus, the decreased plasma oxytocin together with reduced OXTR in the skeletal muscle of Zucker fatty rats may contribute to reduced muscle mass (Kemp et al 2009) and the reduced muscle glucose disposal observed in obesity and insulin resistance (King et al 1992). Based on muscle OXTR protein data and muscle membrane oxytocinase activity, we conclude that there is reduced oxytocin processing in the tissue under the conditions of obesity.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, the decreased plasma oxytocin together with reduced OXTR in the skeletal muscle of Zucker fatty rats may contribute to reduced muscle mass (Kemp et al 2009) and the reduced muscle glucose disposal observed in obesity and insulin resistance (King et al 1992). Based on muscle OXTR protein data and muscle membrane oxytocinase activity, we conclude that there is reduced oxytocin processing in the tissue under the conditions of obesity.…”
Section: Discussionmentioning
confidence: 82%
“…There is confusion on how to interpret changes in lean mass associated with muscle separately from non-muscle fat-free mass, that is, liver, intestine, kidney, and heart, which indeed might be enlarged with the development of obesity (Masgrau et al 2012). Studies on rodents demonstrated that muscle mass was not changed under conditions of DIO (Chanseaume et al 2007), whereas reduced muscle mass was found in genetic models of obesity (Kemp et al 2009). In a study of sequential changes of protein synthesis in two types of skeletal muscles during longterm DIO, Masgrau et al (2012) showed that the muscle mass of rats increased in the initial phase (16 weeks fed HFD) and decreased in the second phase (from 16 to 24 weeks fed HFD) of obesity development (Masgrau et al 2012).…”
Section: Lean Mass Decreasementioning
confidence: 99%
“…Importantly, our findings that PGC-1α elevates LDH H and diminishes LDH M subunit expression are further corroborated by mouse and human studies on muscle beds with different fiber type compositions. In fact, fast-twitch muscles, which typically express low levels of PGC-1α, display high amounts of LDH M subunits, whereas the LDH complexes in slow-twitch muscles with higher expression of PGC-1α are enriched in LDH H subunits (38,39).…”
Section: 2)mentioning
confidence: 99%